Feasibility randomised controlled trial examining the effects of the Anti-Doping Values in Coach Education (ADVICE) mobile application on doping knowledge and attitudes towards doping among grassroots coaches. Issue 1 (1st October 2020) - Nicholls, Adam Robert; Fairs, Lucas R W; Plata-Andrés, Mar; Bailey, Richard; Cope, Edward; Madigan, Daniel; Koenen, Katrin; Glibo, Iva; Theodorou, Nikolaos C; Laurent, Jean-Francois; Garcia, Gaetan; Chanal, Benoit
Abstract : Objectives: Sports coaches are influential in whether athletes dope, but receive very little antidoping education, particularly within entry-level coaching qualifications. We tested the feasibility of an antidoping intervention, delivered via a mobile application, which was designed to increase coaches' knowledge of doping and to reduce favourable doping attitudes. Methods: A two-arm randomised controlled trial, with grassroots coaches who coach young amateur athletes aged between 14 and 18 years of age, was conducted. The Anti-Doping Values in Coach Education (ADVICE) mobile application included modules on fair play, substances, nutritional supplements, rules and leadership. The primary outcome was the change in doping knowledge, 6 weeks after receiving the mobile application. The secondary outcome was changes in doping attitudes. Results: Grassroots coaches (n=200; aged between 18 and 71 years, with between 1 and 42 years of coaching experience) from 29 different countries completed baseline assessments, and 85 completed follow-up assessments, and were included in mixed analysis of variance analyses. The intervention increased coaches' knowledge about doping and also reduced favourable doping attitudes in the experimental arm. Conclusion: The ADVICE mobile application is a feasible method for delivering and increasing grassroots coaches' knowledge of banned substances and the potential side effects of doping. Mobile application-based resources could facilitate a much wider dissemination of antidoping education.